Analysis of concrete structures by fracture mechanics : proceedings of a RILEM Workshop dedicated to Professor Arne Hillerborg, Abisko, Sweden 1989 /: proceedings of a RILEM Workshop dedicated to Professor Arne Hillerborg, Abisko, Sweden 1989. (2014) - Unknown
No abstract available